J05 The association of the ACE gene I/D polymorphism and in-game performance in elite Rugby Union players - Martin, Daniel; Stebbings, Georgina; Heffernan, Shane; Erskine, Rob; Callus, Peter; Brazier, John; Antrobus, Mark; Williams, Alun (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Genetic variation has been proposed as a factor in human athletic performance. The angiotensin converting enzyme (ACE) gene has been studied extensively albeit with heterogeneous results. The insertion (I) and deletion (D) alleles have been associated with altered serum and tissue ACE, as well as endurance- and power-based performance respectively. It is suggested the distinction in rugby union performance can be partly attributed to variations in the ACE gene. The aim of this study was to identify associations between the ACE I/D genetic polymorphism and in-game performance in elite (≥ 5 games at top-flight) rugby union athletes. The athlete cohort consisted of 347 Caucasian men, divided into positional groups (backs and forwards) and positional subgroups (front five, back row, halves, centres, and back three). Ethical approval was provided by Manchester Metropolitan University with written informed consent obtained from all participants. Genotyping and genotype analysis was performed using a combination of the X9 High-Throughput Genomics System (Standard BioTools) and the StepOnePlus™ Real-Time PCR System (Applied Biosystems) and their respective corresponding software. IBM SPSS Statistics 28 (SPSS, Chicago, IL) software was used to conduct Pearson's Chi-square (χ2) test of independence comparing genotype and allelic frequencies and the Kruskal-Wallis H and Mann-Whitney U tests to investigate differences between genotypes. Genotypic and allelic frequencies did not differ at the population level, nor at the positional group/subgroup levels. Performance did not differ between genotypes nor alleles at the population and positional group levels. Back row II genotypes beat more defenders than IDs (P = 0.008) but completed fewer tackles than both IDs (P = 0.05) and DDs (P = 0.013). Halfback DDs missed fewer tackles than both IDs (P = 0.003) and IIs (P = 0.01). Centre DD genotypes made more carries than IIs (P = 0.006). Back three IIs scored more tries than both IDs (P = 0.005) and DDs (P = 0.007) and made more clean breaks than IDs (P = 0.004). Most of the existing literature has been concerned with identifying the ACE gene as a marker of elite performance. To our knowledge, this is the first study to elucidate how the inter-personal differences in rugby union performance are influenced by the ACE I/D polymorphism. The findings from this study may provide novel insight into the specialisation of training and rehabilitation modalities for athletes, based on their genetic makeup.